Ecological Dynamics of Mycobacterium marinum in Aquatic Environments: Interplay of Environmental Parameters and Bacterial Growth Patterns - Ramzan, Muhammad; Matloob, Amina; Ahmed, Usama Bin; Khan, Mohsin; Abbas, Khurram Javed (American Journal of Biology and Natural Sciences, 2025)
This study delves into the intricate ecological dynamics of Mycobacterium marinum and Mycobacterium marinam in aquatic environments, exploring the synergistic interplay between environmental parameters and the patterns of bacterial growth. By integrating field sampling techniques, physicochemical analyses, and controlled laboratory experiments, this study aims to unveil the complex relationships between temperature, pH, dissolved oxygen levels, electrical conductivity, and the survival strategies of these mycobacterial species. Anticipated results are expected to shed light on the adaptive responses of M. marinum and M. marinam to varying environmental conditions, providing valuable insights into their ecological niches and potential implications for ecosystem health and public well-being.